The Effectiveness of Grammatical Hunting Game Method Students’ Arabic Learning Motivation - Shodiq, Muhammad Jafar; Zakiyah, Zaimatuz; Hajib, Zainal Abidin (Universitas Islam Negeri Raden Intan Lampung, 2021)
This experimental research was motivated by the low Arabic learning motivation in class VIII MTsN 9 Bantul which was caused by the use of monotonous learning methods. This study aims to find out students' Arabic learning motivation after the application of Grammatical Hunting language educational game method and to compare the Arabic learning motivation of the experimental class and the control class. This study used a quasi-experimental research type. The sample of this research was students of class VIII B and VIII C of MTsN 9 Bantul Yogyakarta consisting of 60 students. Data were collected through observation, interviews, questionnaires, and documentation. The results of this study indicated that: 1) The student's Arabic learning motivation increased after the application of Grammatical Hunting language educational game method based on the results of the paired sample t-test with a significance value of 0.000 < 0.05, Ha was accepted. 2) There was a significant difference in the learning motivation of the experimental class and the control class, based on the results of the independent sample t-test with a significance value of 2.042 ≥ 2.001, Ha was accepted. This method could increase students' motivation to learn Arabic. This study contributed to the use of varied learning methods, so that qawā'id learning would become an enjoyable learning.